Exercise in patients with metastatic prostate cancer: A comprehensive review - Muñoz-Carrillo, F Javier (2025)
Prostate cancer (PC) is one of the most prevalent malignancies worldwide. Metastatic PC remains an incurable disease, with the androgen receptor (AR) pathway being the primary driver of tumor progression and the main target for therapeutic strategies. Thus, patients usually undergo long-term treatments, particularly androgen deprivation therapy (ADT), which can worsen the intrinsic deterioration in quality of life (QoL) caused by the disease burden. Increasing evidence supports the use of physical activity (PA) and structured exercise (EX) as complementary measures to mitigate treatment-related adverse effects and improve clinical outcomes across tumor types. EX has shown benefits across multiple systems and plays a significant role in modulating tumor progression through several cellular pathways. Furthermore, it has confirmed potential to alleviate cancer-related symptoms while enhancing functional capacity and tolerability of treatment. This review gathers the current evidence regarding the impact of PA and EX on patients with metastatic PC, integrating both epidemiological and interventional studies. Despite promising findings, most of the available evidence is documented on non-metastatic populations, highlighting the need for directed studies in advanced disease settings. Future research is needed in metastatic PC patients, in order to assess long-term impacts of EX in this population.